AWS Certified Security Specialty All-In-One Exam Guide (Exam SCS-C01). - Pierce, Tracy; Rosa, Alex Fernandes (McGraw-Hill Education, 2021)
This self-study resource offers complete coverage of every topic on the AWS Certified Security Specialty exam Take the AWS Certified Security - Specialty exam with confidence using the detailed information contained in this effective self-study resource. Written by a team of AWS insiders, the book shows how to develop, deploy, and maintain robust security protocols on Amazon Web Services. AWS Certified Security Specialty All-in-One Exam Guide (Exam SCS-C01) covers every objective for the exam and provides comprehensive content on cloud-based security. To aid in study, each chapter includes exam tips, chapter summaries, and practice questions that simulate those on the live test. Designed to help you pass the exam with ease, this hands-on guide also serves as an ideal on-the-job reference. Covers all exam topics, including: Cloud security event investigation Cloud security event remediation and planning Monitoring with Amazon CloudWatch Enhanced security monitoring and compliance with AWS services Logging on AWS AWS cryptographic services and tools Designing edge security on AWS Designing and implementing a secure network infrastructure Troubleshooting a secure network infrastructure Designing and implementing host-based security AWS identity and access management Troubleshooting authorization and authentication services Online content includes: 130 practice exam questions Fully customizable exam engine Downloadable code.